Duration of Contact, Type of Leprosy, And Floor Condition As Risk Factors For Leprosy Sero-positivity (KEMAS: Jurnal Kesehatan Masyarakat, 2017)
The high number of leprosy seropositivity in a population may lead to clinical leprosy. This study aimed to identify risk factors of leprosy. This study was conducted in Brondong, Lamongan, East Java. The subjects were 153 people who lived with leprosy patient. lgM anti PGL-1 level was examined used ELISA (Dako). Logistic regression was conducted to test the independent variables. The results showed that the subjects had an average age 31 year (±6.5), average BMI 22 (±2.9) and average IgM anti PGL-1 level 1041 unit/ml (±820). 79.7% of the research subjects were women. The subjects’ house floor condition (p value 0.009) was the most influential variable to seropositivity of leprosy. Our findings indicated that not only the duration of leprosy and the contacts need to be considered in the transmission of leprosy, but also environmental factors, such as the subjects’ house floor condition.